Side Channel Attack Countermeasure for Low Power Devices with Aes Encryption - Abarzua-Ortiz, R; Valencia-Cordero, C (Institute of Electrical and Electronics Engineers Inc., 2021)
The advancement of Internet of Things produces a massive increase in the use of low-power devices, which can contain sensitive information. Most of these devices do not have the necessary security to protect their information. Therefore, the work aims is analyze and compare countermeasures for SCA in low-power devices with 128-AES encryption. In this scenario, we analyze existing countermeasures and conclude that algorithm-based countermeasures are more suitable for low-power devices. Subsequently, we run a set of tests to understand the scope of CPA attacks and thus establish a countermeasure that is tailored to these devices. Finally, we propose a countermeasure based on byte logic, comparing it with traditional countermeasures of the same type. © 2021 IEEE.